Climate Change or Climate Variability? History, Science and Politics in the Mesoamerican Climate - Poleo, Daniel (2016)
Climate variations in Mesoamerica have influenced the development and decay of populations from the earliest human settlements. The present time is no exception; there is no evidence that global warming will impact rainfall in the region, but rather there are important studies showing a response of rainfall to climate variability in the American tropics. Since our tropical region is vulnerable to climate variability, public policies must be congruent to avoid the mistakes of previous generations and achieve, with the help of science, a real progress in the fight against global warming.